NEW FORMS AND TECHNOLOGIES OF INSULIN THERAPY IN TYPE 1 DIABETES - A SYSTEMATIC LITERATURE REVIEW - Agata Ogórek,; Aleksandra Kaniak,; Julia Andrzejewska,; Agata Wińska,; Hanna Pietruszewska,; Irmina Czerepak,; Izabela Majchrzak,; Michał Ziemba,; Klaudia Zackiewicz,; Julianna Zielska, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Type 1 diabetes is a chronic autoimmune disease that leads to permanent lack of insulin. In recent years, advances in insulin formulations and delivery methods have improved the ability to mimic natural insulin secretion and support better diabetes management.Aim: The aim of this article is to review the most commonly used forms of insulin therapy and modern technologies supporting the treatment of type 1 diabetes, with attention to their effectiveness, safety, and impact on patients’ quality of life.Methods: A search of PubMed and ScienceDirect was performed for publications from January 2008 to June 2025. The review included clinical trials and review articles about insulin therapy in type 1 diabetes. Titles and abstracts were screened, full texts were analysed, and reference lists of key papers were checked.Results: Modern insulin therapy is based on insulin analogues with different action profiles and on delivery systems such as insulin pens, pumps, and hybrid closed-loop devices. New basal and prandial analogues help improve glycaemic control and reduce complications. Automated Insulin Delivery systems increase time in range and improve daily functioning. However, problems such as variability of insulin absorption, lipodystrophy, and high costs still remain.Conclusions: Although progress in insulin therapy has improved diabetes care, further research, better access to modern technologies, and further patient education is essential.